Möjligheterna att införa ett kronvittnessystem i svensk rätt - En jämförelse mellan kronvittnessystem och konkurrenslagens eftergifts- och nedsättningsprogram. - Qvarnström,Johanna (2014)
The ideology of criminal justice that rule the Swedish justice system determines which acts that are to be the subject of criminalization and which principles determine the choice of sentencing and penalties. The Swedish Penal Code underwent a large reform in 1989 where equitable grounds were introduced in chapter 29 § 5 of the Swedish Penal Code. The court shall take the defendant´s personal circumstances in consideration and the court will also take the clemency pleas in consideration in order to eliminate penalties from being viewed as unreasonable or unfair. Since the imposition of the clemency pleas there has been a discussion regarding expanding the equitable grounds to comprehend the revelations of other people’s crime. In the Swedish state official reports there has been a notion that an expansion of chapter 29 § 5 of the Penal Code would be unsuitable since the disadvantages were deemed exceeded than the benefits. The aim of this essay was to investigate the Swedish legal situation regarding the possibility of clemency pleas when a accused reveals other people´s crimes. The Swedish Supreme Court only has one precedent regarding the question, NJA 2009 p.599, in which the Supreme Court considered in which regard a clemency plea can be given to an accused that has cooperated in an investigation and revealed other people´s crimes. The Swedish Supreme Court ruled that a clemency plea cannot be given solely on that basis but a penal discount can be given if the accused is the subject of threats for his life and health, and if he because of the revelation never will be able to live a normal life. The precedent has been the subject to debate if it can be considered an introduction of a crown witness system in Swedish law by allowing the revelation of other people´s crimes as one of the penal discounts in chapter 29 § 5 of the Swedish Penal Code. The conclusion of the essay is that NJA 2009 p.599 partially has proven that there is a possibility to give a penal discount for the revelation of other people´s crimes. Even despite there is no explicit ground in the Swedish state official report the question regarding the extent of the clemency pleas have been left open to be ruled by the Swedish Supreme Court’s precedent. In this essay I will compare a crown witness system with the Swedish cartel leniency program. The purpose of the leniency program is to counteract cartels by offering to deduct or eliminate the fine for participating in a cartel for the companies that choose to collaborate with the Swedish Competition Authority to prosecute the members of the cartel. In order to achieve an efficient competition it is required that cartels and restrictive practices are prohibited. The companies that participate in a cartel will be prosecuted with a fine for participating in a cartel. The purpose of the fine is to work as deterrence and counteract the creation of cartels. To allow a complete deduction of a sentence is regarded to be contrary to Swedish law tradition but nevertheless the Swedish cartel leniency program has been regarded as passable with Swedish law. The purpose of this essay is to investigate the basis of this reasoning.